The issues of cultural expressions untranslatability from Iraqi Arabic into English language - Ahmed Mohamed Fahid ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This study aims at explore the cultural untranslatability for expressions found in Iraqi culture. Different expressions have been chosen from Iraqi environment, which are widely used in Iraqi tongue, as a sample of the research. The researcher tries to show the cultural dimension for each expression and then explain why these expressions are untranslatability. The study found out that some Iraqi expressions are unable to translate due to the religious, ethical, psychological, and tribal dimensions that effect on the Iraqi people life to produce such expressions. The study showed that the impact of such dimensions is limited to Iraqi cultural aspects, because it has no similarities in other cultures.